Inovasi Seni sebagai Sarana Pemberdayaan Ekonomi dan Sosial di Desa Jambeyan - Siti Ridloah; Astri Arum; Cici Everil Leviana Dewi; Siska Alfillia Nova; Fairuz Zahira Hanun (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Family Empowerment and Welfare (PKK) is a community organization created to help families with the aim of improving community welfare. PKK plays an important role in improving skills and opening new opportunities in the family economy and improving the quality of life. One of the PKK empowerments carried out by the community service team is to hold bead and ecoprint training which aims to improve skills, creativity, economic empowerment, and preserve the environment using natural materials. The beads and ecoprint training organized for PKK women in Jambeyan Village aims to increase skills, creativity, and community income. The method used in this training involves two stages, namely planning and implementing activities. The focus of the workshop activities was on socialization and training of beads and ecoprints to representatives of the Jambeyan Village PKK. An introduction to beads and ecoprints, activity mapping, and practical instructions for making beads and ecoprint tote bags are part of this training. The training was considered successful because the attendance and participation plans of participants had met the requirements.